THE EFFECT OF COOPERATIVE LEARNING TYPE TGT USING CONCEPT MAPS TOWARDS STUDENTS’ LEARNING OUTCOMES ON FLUID DYNAMICS TOPIC GRADE XI SMA NEGERI 5 BINJAI A.Y. 2012/2013 - Debora Betty Sitanggang; Mara Bangun Harahap (UNIVERSITAS NEGERI MEDAN, 2013)
ABSTRACT The purpose of this research is to know the effect of cooperative learning type TGT using concept maps towards students’ learning outcomes on fluid dynamics topic grade XI SMA Negeri 5 Binjai A.Y. 2012/2013. The type of research is quasi experimental research. The population is all students of class XI IPA SMA Negeri 5 Binjai Academic Year 2012/2013, consist of four classes. Two classes is selected randomly as sample. One class as experiment class treatment using cooperative learning type TGT using concept maps and another class as control class using direct instruction. Data is tested is normal distribution and homogeny. To do hypothesis test used with t one tailed. Testing of hypothesis for posttest showed that tcount > ttable. Based on the observation about students’ affective, psychomotor, and activity that done by observers showed that experimental class higher than control class. This case means there are differences of students’ learning outcomes caused by effects of cooperative learning type TGT using concept maps on fluid dynamics topic grade XI SMA Negeri 5 Binjai A.Y. 2012/2013. Key words: Cooperative learning type TGT, Concept Maps, Students Learning Outcomes